2009
DOI: 10.1074/jbc.m808209200
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Structure of Neisseria meningitidis Lipooligosaccharide from the M986 Strain and Three of Its Variants

Abstract: Neisseria meningitidis is a cause of fatal sepsis and epidemic meningitis. A major virulence factor is cell wall lipooligosaccharide (LOS). The M986 strain has been used extensively in immunological and vaccine research. Yet, the LOS repertoire of this strain is not known. Here we have investigated the LOS structures of M986 and three of its variants OP1, OP2؊, and OP2؉. This strain and its variants present a series of related LOS families that are increasingly truncated in their listed order. The major struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Our recent work with a large group of carrier and disease-causing strains of N. meningitidis showed that lipid A phosphorylation states can also be correlated with clinical outcomes [13]. The inset above Figure 1a shows a proposed structure for the major LOS species at m/z 4087.76 in N. meningitidis 89I that represents a prototypical Neisserial LOS structure [9,[46][47][48]. The detailed lipid A and oligosaccharide structures depicted for the N. meningitidis 89I LOS, an L4 immunotype [49], are based on MS and NMR studies of the conserved Neisserial lipid A [50] and the L4 oligosaccharide [42].…”
Section: Molecular Weight Profiling Of Intact Losmentioning
confidence: 99%
“…Our recent work with a large group of carrier and disease-causing strains of N. meningitidis showed that lipid A phosphorylation states can also be correlated with clinical outcomes [13]. The inset above Figure 1a shows a proposed structure for the major LOS species at m/z 4087.76 in N. meningitidis 89I that represents a prototypical Neisserial LOS structure [9,[46][47][48]. The detailed lipid A and oligosaccharide structures depicted for the N. meningitidis 89I LOS, an L4 immunotype [49], are based on MS and NMR studies of the conserved Neisserial lipid A [50] and the L4 oligosaccharide [42].…”
Section: Molecular Weight Profiling Of Intact Losmentioning
confidence: 99%
“…OS Compositions-A number of groups, including our own, have studied the structure of the OS from N. meningitidis (1, 23, 24,26,32,33). Compositions for the OS were assigned based on peaks we detected, the previously reported structures, and using the following potential components: 2 Kdo, 2 Hep, 1 or more Hex, and 1 or more HexNAc, 0 -1 Neu5Ac, 0 -1 O-Ac, 0 -1 O-Gly, and 0 -2 PEA.…”
Section: Relative Abundance Of Lipid a Phosphoforms Correlates With Tmentioning
confidence: 99%
“…It is anchored in the outer bacterial membrane by lipid A, and two heptoses (Hep I and Hep II) branch from KDO I (2-keto-3-deoxyoctulosonic acid) carrying the short oligosaccharide side chains (47,70). A structural model of the LPS of the N. meningitidis strain MC58 (serogroup B, ST-32, immunotype L3) integrating recent research and nuclear magnetic resonance (NMR) analysis (28,47,50,66,75) is depicted in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%